Avaliação física e fotocatalítica de peças porosas de ZnO obtidas por consolidação por amido - Neves, Paula Guimarães (2021)
Dyes are substances used in industrial processes (textile industries) and are considered a harmful waste if disposed inappropriately in water resources. Therefore, there is a great need to study and apply techniques that allow the removal of dyes from industrial effluents such as the Advanced Oxidative Processes (POA's). Heterogeneous photocatalysis (a type of POA) consists of the activation of a semiconductor by radiation, which generates oxidizing and reducing sites that will operate in order to minimize pollutants in water. The surface area of a semiconductor is of extreme importance once the processes will activate and occur on it. Within this context, researches that address the use of solid pieces for photocatalytic purposes are few and not too explored. It is extremely relevant that the finished product has high porosity, so the light permeates it and generates photocatalysis; Also, it needs to contain enough mechanical resistance to prevent premature rupture. Porous ceramics are typically fragile; therefore, the search for conformation and subsequent sintering techniques that balances porosity and mechanical strength is justified. This work studied the obtention of porous ceramics from Zinc oxide through a not yet explored technique: starch conformation and its application as catalysts in the photocatalytic degradation of the Rhodamine B dye. Pieces with different mass ratios of ZnO and starch (10, 20, 30, 40 and 50% by mass of starch) were produced and characterized in green. After the heat treatment (heating rate of 1C / min, firing level of 120 minutes and firing temperature at 800C), pieces were characterized by determining their physical properties and photocatalytic assays were carried out. Photocatalytic activity was evaluated through the decomposition of Rhodamine B (RhB) when exposing the piece to UV light radiation; it was also investigated the proximity of samples in relation to the source of radiation in the RhB solution. The viability of the technique was proven by obtaining apparent porosity values of 64,24%. The greater the proximity of light the greater the photocatalytic activity for RhB degradation, obtaining results up to 79,19%.